Penguatan Pengetahuan Dan Sikap CPPOB Melalui Media Ular Tangga Pada Siswa SMKN 4 Madiun - Novianti Tysmala Dewi; Amalia Ruhana; Noor Rohmah Mayasari; Raisya; Idcha Kusma Ristanti; Rita Ismawati; Veni Indrawati (STMIK Royal, 2026)
Abstract: Food safety is an essential aspect of ensuring the quality and health of food products, particularly for vocational students who will become future workers in the culinary industry. Understanding and maintaining positive attitudes toward hygiene and sanitation should be developed during the learning process to build appropriate food safety practices. This community service program aimed to strengthen students’ knowledge and attitudes regarding hygiene and sanitation through Good Processed Food Production Methods (CPPOB) education using a CPPOB Snakes and Ladders interactive learning media. The activity involved 52 culinary students of SMKN 4 Madiun, consisting of 10 males and 42 females. The program was conducted in three stages: interactive material delivery, discussion and Q&A sessions, and an educational game session. Evaluation was carried out using pre-test and post-test to measure changes in knowledge and attitudes. The results showed an increase in the average knowledge score from 93 to 99 and attitude score from 88 to 93 after the intervention. These findings indicate that interactive educational media effectively enhance students’ conceptual understanding and foster positive attitudes toward hygiene and sanitation practices. This program can serve as an innovative learning model to improve vocational students’ competencies in culinary education. Keywords: CPPOB; education; hygiene and sanitation; snakes and ladders media; culinary students Abstrak: Keamanan pangan merupakan aspek penting dalam menjamin mutu dan kesehatan produk makanan, khususnya bagi siswa kejuruan yang akan menjadi tenaga kerja di bidang kuliner. Pemahaman dan sikap positif terhadap higiene dan sanitasi perlu ditanamkan sejak masa pendidikan agar terbentuk perilaku kerja yang sesuai dengan prinsip keamanan pangan. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan pengetahuan dan membentuk sikap positif siswa jurusan kuliner SMKN 4 Madiun melalui edukasi Cara Produksi Pangan Olahan yang Baik (CPPOB) berbasis media permainan ular tangga. Kegiatan diikuti oleh 52 siswa, terdiri atas 10 laki-laki dan 42 perempuan. Pelaksanaan dilakukan melalui tiga tahap, yaitu penyampaian materi interaktif, sesi diskusi dan tanya jawab, serta permainan edukatif. Evaluasi menggunakan pre-test dan post-test untuk mengukur perubahan pengetahuan dan sikap siswa. Hasil menunjukkan adanya peningkatan rata-rata skor pengetahuan dari 93 menjadi 99, serta sikap dari 88 menjadi 93 setelah edukasi. Peningkatan ini menunjukkan bahwa penggunaan media edukatif interaktif efektif dalam memperkuat pemahaman konsep sekaligus membentuk sikap positif siswa terhadap penerapan higiene dan sanitasi pangan. Kegiatan ini dapat menjadi model pembelajaran inovatif bagi sekolah kejuruan dalam meningkatkan kompetensi siswa di bidang kuliner. Kata kunci: CPPOB; edukasi, higiene sanitasi; media ular tangga; siswa kuliner